(untitled) (Estudios Sociales, 2024)
The article presents advances of a research that characterizes the strategies with which developers of land destined for open neighborhoods in Santa Fe and adjoining cities organize their economic activity. The in–depth interviews conducted report that these actors accept non–optimal, but situationally appropriate profitability and apply learnings from their experience (selection of investors, pre–sale, retention of parcels based on the buyer’s profile). The State is criticized for «changing the rules of the game» and for lacking agility in processing urbanization projects, a fact that extends the capital turnover period and increases the uncertainty for developers, who try to counteract this by increasing economic profit margins. The conclusions suggest the advisability of a) testing regulations under which the State approves an urbanization procedure after a certain assigned time expires and b) encouraging the sale of parcels by applying strong surcharges and/or compulsory urbanization ordinances on idle properties.